Comparison of the effect of traditional Chinese medicine injection combined with chemotherapy and chemotherapy alone on the prognosis, quality of life and immune function in patients with ovarian carcinoma: A protocol for systematic review and network meta-analysis. Issue 41 (15th October 2021) - Xu, Xingnong; Zhu, Li; Long, Lin
Abstract: Background: The effectiveness of traditional Chinese medicine (TCM) in assisting the reduction of the toxic effects of chemotherapy and enhancing the efficacy of chemotherapy is gradually being recognized. Traditional Chinese medicine injection (TCMJ) has been widely used as a promising adjuvant drug in the treatment of ovarian carcinoma. However, the exact clinical efficacy and safety of TCMJ have not been well studied due to the wide variety. This study aims to conduct a network meta-analysis of randomized controlled trials (RCTs) about comparing the effect of TCMJ combined with chemotherapy and chemotherapy alone on the treatment of ovarian cancer, thus summarizing the effects of TCMJ on the prognosis, quality of life and immune function of ovarian carcinoma patients, and providing a reference for developing therapeutic regimens for ovarian carcinoma. Methods: Randomized controlled trials reporting the effect of TCMJ combined with chemotherapy and chemotherapy alone on the prognosis, quality of life and immune function in patients with ovarian carcinoma published before September 2021 will be screened out from online databases like PubMed, Web of Science, Scopus, Cochrane Library, Embase, China Scientific Journal Database, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, and Wanfang Database. Subsequently, 2 researchers will be independently responsible for literature screening, data extraction and assessment of their quality. All data will be processed by R.4.1.0. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusions: Evidence-based medicine supports the efficacy and safety of TCMJ combined with chemotherapy for the treatment of ovarian carcinoma, which is better than that of chemotherapy alone. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/P93VJ.